Cover Picture: Increased open‐circuit voltage of ZnO nanowire/PbS quantum dot bulk heterojunction solar cells with solution‐deposited Mg(OH)2 interlayer (Phys. Status Solidi RRL 10/2016). Issue 10 (18th October 2016) - Zang, Shuaipu; Wang, Yinglin; Su, Wei; Zhu, Hancheng; Li, Gang; Zhang, Xintong; Liu, Yichun
Abstract : No abstract is available for this article. Abstract : Bulk heterojunction (BHJ) structure offers an opportunity to eliminate the charge‐extraction limit in planar‐heterojunction colloidal quantum dot solar cells (CQDSCs), but the manyfold increase in interfacial area leads to the increased interfacial charge recombination and the reduced open‐circuit voltage ( V oc ). Shuaipu Zang et al. (pp. 745–748 ) utilized a solution‐deposited ultrathin Mg(OH)2 layer to improve the performance of BHJ CQDSCs composed of ZnO nanowires and PbS quantum dots. This Mg(OH)2 interlayer efficiently passivated the surface defects of ZnO nanowires and provided a tunnel barrier at the ZnO/PbS interface. As a result, the charge recombination at ZnO/PbS interface was largely suppressed, which was proved by the significantly elongated lifetime of charge carriers and the increased V oc of the Mg(OH)2 ‐involved BHJ CQDSCs. Careful thickness optimization of Mg(OH)2 interlayer finally brought a ∼33% increase in V oc and ∼25% improvement in power conversion efficiency. The convenient and effective method for constructing an ultrathin Mg(OH)2 interlayer could also be introduced in the further improvement of PbS CQDSCs and other type of solar cells.